2015
DOI: 10.1016/j.celrep.2015.06.053
|View full text |Cite
|
Sign up to set email alerts
|

A Pooled shRNA Screen Identifies Rbm15, Spen, and Wtap as Factors Required for Xist RNA-Mediated Silencing

Abstract: SummaryX-chromosome inactivation is the process that evolved in mammals to equalize levels of X-linked gene expression in XX females relative to XY males. Silencing of a single X chromosome in female cells is mediated by the non-coding RNA Xist. Although progress has been made toward identifying factors that function in the maintenance of X inactivation, the primary silencing factors are largely undefined. We developed an shRNA screening strategy to produce a ranked list of candidate primary silencing factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
300
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(309 citation statements)
references
References 40 publications
5
300
4
Order By: Relevance
“…Alternatively, although lincRNAs interact with PRC2, this interaction may not be required for Polycomb recruitment, with the lincRNA instead repressing gene expression by another mechanism, which then allows for Polycomb recruitment (Brockdorff 2013). For example, a number of studies recently determined that Xist RNA interacts with the transcriptional repressor SPEN (also known as SHARP) and that this is required for gene silencing (Chu et al 2015;McHugh et al 2015;Minajigi et al 2015;Moindrot et al 2015;Monfort et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, although lincRNAs interact with PRC2, this interaction may not be required for Polycomb recruitment, with the lincRNA instead repressing gene expression by another mechanism, which then allows for Polycomb recruitment (Brockdorff 2013). For example, a number of studies recently determined that Xist RNA interacts with the transcriptional repressor SPEN (also known as SHARP) and that this is required for gene silencing (Chu et al 2015;McHugh et al 2015;Minajigi et al 2015;Moindrot et al 2015;Monfort et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our RNAi screen targeting splicing factors did not identify any new additional sex determination genes, indicating that there are a limited number of genes yet to be identified in this pathway. Finally, intriguingly, three recent studies have identified SPEN and Rbm15 (the mouse and human ortholog of Nito) as factors interacting with Xist, the long noncoding RNA that is essential for dosage compensation in mammals (36)(37)(38). Clearly, future experiments such as RNA-seq will be necessary to elucidate the mechanism and logic of Nito-mediated signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…These initial Xist-coated DNA regions (black regions) sample different locations of the nucleus (44,45,23,46,47) and when they come into close proximity of the nuclear lamina, are sequestered at the nuclear lamina through an interaction between Xist and LBR (middle panel). Because DNA that interacts with the nuclear lamina undergoes more constrained mobility (23,24), this recruitment changes the 3-dimensional organization of X-chromosome (15,48,49) and repositions active genes (green regions) closer the Xist transcription locus enabling Xist, and its SHARP/SMRT/HDAC3 silencing complex (11,18,22), to spread to these new sites by 3-dimensional proximity transfer. These sites are then recruited to the nuclear lamina, effectively bringing another set of active genes (yellow regions) into closer contact with the Xist transcription locus (right panel).…”
Section: Fig S6 δRs-lbr and δTm-lbr Localize Properly In The Nucleamentioning
confidence: 99%